2016
DOI: 10.4172/2165-8064.1000257
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Direct Carbonizable Phenolic Resin-based Nanofibers

Abstract: The total nonvolatile concentration of the spinning dope was kept constant at 10 wt% changing the composition of the materials (Table 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Kawahara also used similar systems to produce well-defined precursor fibres with nanoscale diameter for carbon nanofibers using electrospinning with resol-phenol formaldehyde resin, keratin and PVOH dissolved in water as the spinning dope. The author suggested that the obtained electrospun fibres could be directly carbonized to produce non-woven carbon nanofiber fabrics [256].…”
Section: Phenol-formaldehyde Resinsmentioning
confidence: 99%
“…Kawahara also used similar systems to produce well-defined precursor fibres with nanoscale diameter for carbon nanofibers using electrospinning with resol-phenol formaldehyde resin, keratin and PVOH dissolved in water as the spinning dope. The author suggested that the obtained electrospun fibres could be directly carbonized to produce non-woven carbon nanofiber fabrics [256].…”
Section: Phenol-formaldehyde Resinsmentioning
confidence: 99%
“…Thermosets can also be part of the electrospinning process (76). Polymer fibres can be spun directly from resin, where the curing is inhibited before or during the collection process (77,78). The process can also include the co-spinning of a thermoset and a thermoplast (79,80).…”
Section: Polymer Materialsmentioning
confidence: 99%